Online Freelance Marketplaces as a Business Opportunity - Tawami, T; Djauhari, H A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to analyze the development and benefits of online freelance marketplaces for freelancers. The research method used in this paper was descriptive method which described and compared social problems based on facts, theories, and accurate reference sources. The results of this study were to explain that online freelance marketplaces had an important role in increasing business opportunities for freelancers. Online freelance marketplaces can be used as jobs for them without having to be bound by multiple customers and capabilities. They can freely have as many customers as they can. Of course, this needs to be done by freelancers who want to earn new income.